2017
DOI: 10.1038/s41598-017-17752-w
|View full text |Cite
|
Sign up to set email alerts
|

Immune microenvironment of experimental rat C6 gliomas resembles human glioblastomas

Abstract: Glioblastoma (GBM) is the most aggressive primary brain tumor, with ineffective anti-tumor responses and a poor prognosis despite aggressive treatments. GBM immune microenvironment is heterogenous  and activation of specific immune populations in GBM is not fully characterized. Reliable animal models are critical for defining mechanisms of anti-tumor immunity. First we analyzed the immune subpopulations present in rat C6 gliomas. Using flow cytometry we determined kinetics of infiltration of myeloid cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 85 publications
4
76
0
Order By: Relevance
“…Similarly, in human glioma samples obtained from patients, (Monif et al, 2014) observed P2X7 overexpression in the tumor when compared to the normal brain, especially in the glioma cells on the tumor periphery, but also in the microglia and, to a lower extent, in the astrocytes associated with the tumor. Concordantly, it is known from long time that activated microglia show increased activation of P2X7 receptor in various pathological states (Ferrari et al, 1999;Ferrari et al, 1997;Hide et al, 2002) and it is well established that it contributes to the glioma-supporting microenvironment (Gieryng et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, in human glioma samples obtained from patients, (Monif et al, 2014) observed P2X7 overexpression in the tumor when compared to the normal brain, especially in the glioma cells on the tumor periphery, but also in the microglia and, to a lower extent, in the astrocytes associated with the tumor. Concordantly, it is known from long time that activated microglia show increased activation of P2X7 receptor in various pathological states (Ferrari et al, 1999;Ferrari et al, 1997;Hide et al, 2002) and it is well established that it contributes to the glioma-supporting microenvironment (Gieryng et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Several evidences indicate the pro-tumorigenic effect of microglia in gliomas (66,(119)(120)(121)(122)(123). In the present study, we identified microglia expressing TLR4 protein around vessels and hypoxic areas.…”
Section: Discussionsupporting
confidence: 64%
“…Additionally, numerous other preclinical studies have highlighted the tumor-promoting and immunosuppressive roles of these cells in GBM [2,[24][25]. However, unlike promising preclinical studies, efforts to deplete TAMCs in GBM patients have been disappointing.…”
Section: Discussionmentioning
confidence: 99%